NICOLE RAFTER - Burton, Chase, author. ([S.l.])
1 online resource
Keywords: This book is a critical summary and exegesis of the work of Nicole Rafter, who was a leading scholar of the history of biological theories of crime causation as well as a profound theorist of the role of history within criminology. It introduces Rafter's key works and assesses her contributions to the fields of feminist criminology, cultural criminology, visual criminology and historical criminology. It also explores her theorization of criminology's identity, scientific status, and possible futures. While many books on criminological theory explain and historically contextualize theory, they do not interrogate the production of theory or the epistemological assumptions behind it. Drawing on the world of Nicole Rafter, this book offers an accessible handbook to her extensive historical studies and to how her work demonstrated the importance of historical theory to criminological knowledge. Furthermore, the author brings Rafter's historical research to life and shows how it speaks to contemporary issues in criminology and punishment. Written in a clear and direct style, this book will appeal to students and scholars of criminological theory, intellectual history, sociology, comparative criminology, and feminist criminology.